The HadGEM2-ES implementation of CMIP5 centennial simulations - Jones, C; Hughes, J; Bellouin, N; Hardiman, S; Jones, G; Knight, J; Liddicoat, S; O'Connor, F; Andres, R; Bell, C; Boo, K; Bozzo, A; et al. (Copernicus GmbH, 2011)
The scientific understanding of the Earth's climate system, including thecentral question of how the climate system is likely to respond tohuman-induced perturbations, is comprehensively captured in GCMs and EarthSystem Models (ESM). Diagnosing the simulated climate response, andcomparing responses across different models, is crucially dependent ontransparent assumptions of how the GCM/ESM has been driven - especiallybecause the implementation can involve subjective decisions and may differbetween modelling groups performing the same experiment. This paper outlinesthe climate forcings and setup of the Met Office Hadley Centre ESM, HadGEM2-ES for the CMIP5 set of centennial experiments. We document theprescribed greenhouse gas concentrations, aerosol precursors, stratosphericand tropospheric ozone assumptions, as well as implementation of land-usechange and natural forcings for the HadGEM2-ES historical and futureexperiments following the Representative Concentration Pathways. Inaddition, we provide details of how HadGEM2-ES ensemble members wereinitialised from the control run and how the palaeoclimate and AMIPexperiments, as well as the "emission-driven" RCP experiments wereperformed. © 2011 Author(s).